Speed Control of Permanent Magnet Synchronous Motor Using Xilinx System Generator - Chafa Mohamed; Kamel, Messaoudi; Lamri, Louze (Automatic control and computer sciences, 2024)
The importance of using variable-speed permanent magnet synchronous motors in various fields requires the use of speed control techniques. This document presents the vector control of permanent magnet synchronous motors based on proportional integrated controllers using the Xinlinx System Generator tool. The implementation based on the use of Xilinx System Generator blocks aims to achieve speed variation of the machine. The obtained implementation and synthesis results have demonstrated the effectiveness and proper functioning of the control, enabling the machine’s speed to remain stable according to the chosen reference. The synthesis allows real-time hardware implementation on the FPGA board using the FPGA in the LOOP technique.